Xanthogranulomatous pyelonephritis in a patient with polycystic kidney disease without underlying risk factors: a case report - Kang, Yoomee; Lee, Tae Won; Bae, Eunjin; Jang, Ha Nee; Jung, Sehyun; Lee, Seunghye; Chang, Se-Ho; Park, Dong Jun (Frontiers in Medicine, 2024)
Xanthogranulomatous pyelonephritis (XGP) is an extremely rare, chronic granulomatous inflammatory condition thought to arise secondary to a combination of obstruction, recurrent bacterial infection and an incomplete immune response although the etiology of XGP is more complex. We would like to report a case of XGP occurring in a patient with polycystic kidney disease (PCKD), which has not been previously documented in etiology. A 29-year-old woman presented to our hospital with right upper quadrant pain for 5 days. She had experienced a lowgrade fever, generalized weakness, and myalgia throughout her body for 2 weeks. She had no history of renal stones or recurrent UTIs. Contrast-enhanced CT revealed a well-enhancing large septated cystic mass in the right kidney and numerous cysts in the liver and both kidneys.Open right radical nephrectomy was performed due to the suspicion of renal cell carcinoma, as there was no response to antibiotics over 7 days. Gross specimen demonstrated architectural distortion due to xanthomatous nodules and a dilated pelvico-calyceal system filled with pus and blood. Microscopic examination revealed infiltration of neutrophils and lipid-laden macrophages. The patient is currently being followed up in the outpatient clinic without recurrence of XGP. This is the first reported case of XGP in a patient with underlying PCKD.Physicians should consider PCKD as a potential underlying cause of XGP.